A violation of monotonicity in a noncooperative setting - Maria Montero; Juan Vidal-Puga (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
A power measure is monotone if a player with a larger weight is assigned at least as much power as a player with a smaller weight in the same weighted majority game. Failure of a power index to satisfy monotonicity is often considered a pathological feature. In this paper, we show that monotonicity may fail in the unique subgame perfect equilibrium of a noncooperative bargaining game. A player with a smaller weight may have a higher expected payoff than a player with a larger weight. This is possible even though coalition formation and payoff division are endogenous, all players are rational and there is no asymmetry between the players other than in the weights.
Keywords: 330; Nichtkooperatives Spiel; Macht; Rationales Verhalten; Verhandlungstheorie; Theorie